[B(O–C6H4–CN)4]– based Silver and Copper Coordination Polymers1. Issue 10 (5th June 2014) - Lund, Henrik; Harloff, Jörg; Schulz, Axel; Villinger, Alexander
Abstract A series of new coordination polymers bearing the [B(O–C6H4–CN)4]– anion was synthesized. Two new, one dimensional coordination frameworks of the type M[B(O–C6H4–CN)4] (M = Ag, Cu) were obtained by salt metathesis. The reactivity towards organic Lewis‐bases was studied. The reaction with bidentate ligands yielded two dimensional networks with the general formula [M(L)][B(O–C6H4–CN)4] {L = 2, 2′‐bipyridine, 4, 4′‐bipyridine, 1, 2‐bis(pyridyl)ethane, 1, 4‐diazabicyclo[2.2.2]octane}. The synthesis, properties and single crystal structure are reported.